Building an optimal portfolio of Sharia-compliant stocks using the Markowitz model: A study of listed JII companies - Ajuna, Luqmanul Hakiem; Dukalang, Hendra; Ardi, Muhammad (Jurnal Ekonomi & Keuangan Islam, 2025)
Purpose – This study analyzes the expected returns and risks associated with these stocks and identifies the optimal portfolio composition.Methodology – This study utilized operational data analysis and the Markowitz model to assess 30 stocks listed on the JII from 2017 to 2020. Through purposive sampling, 13 companies that met the specific sample criteria were selected for analysis.Findings – The analysis successfully identified an optimal portfolio composed of six stocks: ANTM (Aneka Tambang Tbk), ICBP (Indofood CBP Sukses Makmur), INCO (Vale Indonesia Tbk), KLBF (Kalbe Farma Tbk), PTBA (Bukit Asam Tbk), and UNTR (United Tractors Tbk). This portfolio demonstrates an expected rate of return ranging from 0.28% to 1.88%. Notably, the portfolio's overall risk value was calculated to be only 0.19%, which is significantly lower than the individual risk associated with any single stock within the portfolio.Implication – This study provides valuable insights for investors looking to build a balanced and Shariah-compliant investment portfolio, improving their understanding of expected returns and associated risks in Islamic financial markets.Originality – The abstract does not explicitly state the originality section. However, the unique combination of focusing on JII-listed Sharia stocks and applying the Markowitz model to identify an optimal portfolio can be inferred as the original contribution of this study. The context of Islamic financial markets distinguishes it from that of a general investment study.